Handbook of Socioeconomic Determinants of Occupational Health 2020
DOI: 10.1007/978-3-030-05031-3_20-1
|View full text |Cite
|
Sign up to set email alerts
|

Work–Life Balance: Definitions, Causes, and Consequences

Abstract: This chapter reviews the multiple definitions of work-life balance, including definitions focused on the equity of time spent in the work and non-work domains, satisfaction with performance/time spent in each domain, and the salience of each role for an individual. There is a general consensus that a preferred definition should focus on work-life rather than work-family, in order to include non-family responsibilities and demands, such as study or travel commitments. The chapter also discusses the common antec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
3
1

Relationship

4
6

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 60 publications
0
27
0
1
Order By: Relevance
“…Lastly, we also examine work-family balance as an antecedent of parenting stress and marital conflict. Defined as "'the individual perception that work and non-work activities are compatible and promote growth in accordance with an individual's current life priorities" (Kalliath & Brough, 2008, p. 326), work-family balance has been shown to lead to increased family satisfaction and functioning (Brough et al, 2020;Chan et al, 2016). Even though the popular media has often reported that work-family balance has diminished in light of the COVID-19 pandemic and Circuit-breaker, we draw particular attention to the current conceptualization of work-family balance which emphasizes perceptions as opposed to objective measures of "balance".…”
Section: Spousal Support Employer Support and Work-family Balancementioning
confidence: 99%
“…Lastly, we also examine work-family balance as an antecedent of parenting stress and marital conflict. Defined as "'the individual perception that work and non-work activities are compatible and promote growth in accordance with an individual's current life priorities" (Kalliath & Brough, 2008, p. 326), work-family balance has been shown to lead to increased family satisfaction and functioning (Brough et al, 2020;Chan et al, 2016). Even though the popular media has often reported that work-family balance has diminished in light of the COVID-19 pandemic and Circuit-breaker, we draw particular attention to the current conceptualization of work-family balance which emphasizes perceptions as opposed to objective measures of "balance".…”
Section: Spousal Support Employer Support and Work-family Balancementioning
confidence: 99%
“…Employees with high levels of resilience are most likely to successfully balance their work and life (Brough et al. 2020 ). Resilience can be cultivated through multi‐modal interventions focused on enhancing an individual's personal resources (Grant and Kinman 2014 ) as well as daily recovery experiences (Demerouti et al.…”
Section: Accommodating Work and Life Needs During And After The Pandemicmentioning
confidence: 99%
“…Thus, it is vital to learn how to be flexible to not lead to doubts or desire to give up (Holden & Renshaw, 2008). Even though inevitably, there are always competing demands for our times but to achieve a perfect work-life balance Grzywacz and Carlson (2007) argued that work-life balance should consider the impact of an individual's lack of credit on their work and family environment (Brough et al, 2020). It is vital to analyze our goals, especially long-and short-term career plans that are essential and can be sources of motivation as we use them from our time in our day to day living.…”
Section: A Work-life Balancementioning
confidence: 99%